PENGARUH IMPLEMENTASI E-BOOK INTERAKTIF BERBASIS DIGITAL TERHADAP PENGUATAN LITERASI MEMBACA SISWA SEKOLAH DASAR - Banglo, Alfiany; Azisah Intang, Nur; Sumarlin, Lutfia; Nurhaedah; Ramadani, Aulia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of implementing digital interactive e-books on strengthening the reading literacy of elementary school students, while simultaneously identifying factors that influence the effectiveness of their use in learning contexts. The method employed is a Systematic Literature Review (SLR) drawing on data from the SINTA, GARUDA, and Google Scholar databases. A total of 10 scientific journal articles meeting the inclusion criteria were systematically analyzed. The findings indicate that interactive e-books exert a positive and significant impact on improving reading literacy through features such as animation, audio, text-to-speech, video, and educational quizzes. All development studies reported excellent levels of validity and practicality, as well as measurable effectiveness. Nevertheless, limitations in technological devices, internet access, and teacher readiness remain the primary barriers to implementation. It is recommended that the development of interactive e-books be accompanied by strengthening teachers’ digital competencies and the provision of adequate technological infrastructure in schools. Keywords: interactive e-book; reading literacy; digital media; elementary school; systematic literature review